Možnosti uporabe genskega dopinga in problemi njegove detekcije - Žiberna, Lovro (Farmacevtski vestnik, 2007)
Gene doping is defined as the non-therapeutic use of cells, genes, genetic elements, or of the modulation of gene expression, having the capacity to enhance athletic performance. The purpose of gene insertion into the target cells is to improve physiological abilities by vast production of protein thatamplifies or inhibits certain signalling pathways. Insertion of genes for erythropoietin, IGF-1, myostatin inhibitors, VEGF and PPAR-delta in animals has shown major rise in aerobic capabilities, prolonged endurance and increased muscle strength. However, several problems with efficiency and specificity of gene transfer exist and call attention to safety and health concerns. Also, no adequate non-invasive and sensitive detection method exists for gene doping.
Keywords: detekcija dopinga; eritropoetin; genski doping; miostatin